Power management enhancement and smoothing DC voltage using integrated BESS and SMES in Off-grid hybrid AC/DC microgrid based on ILCs - Sara Mahmoudi Rashid; Amir Rikhtehgar Ghiasi (Scientific Reports)
Abstract The random and variable generation of wind and solar energies, particularly in DC microgrids, leads to undesirable fluctuations in the DC link voltage, consequently decreasing the power quality on the DC side. This issue is exacerbated in independent AC/DC hybrid microgrids, where AC and DC subgrids are interconnected via interlinking converters (ILCs), intensifying the voltage fluctuations and severely impacting power distribution in the AC domain. This article proposes a hybrid battery system integrated with a superconducting magnetic energy storage (SMES) system to stabilize voltage fluctuations in the DC link, which occur due to the variable nature of renewable energy sources influenced by weather conditions. The proposed hybrid storage system is applied in an off-grid AC/DC hybrid microgrid, dynamically smoothing the DC link voltage while supporting the grid loads during periods of reduced distributed generation (DG) and enhancing power management between AC and DC microgrids. Additionally, two ILCs with virtual synchronous generator (VSG) control are suggested to enable the integration of AC and DC microgrids. The initial ILC manages the distribution of power between the two microgrids, while the second ILC focuses on improving power quality on the AC side and its DC link to the proposed hybrid storage system. Consequently, the hybrid storage system not only regulates the DC link voltage alongside the second ILC but also controls the DC microgrid voltage. A photovoltaic (PV) unit, coupled with a wind power unit based on a permanent magnet synchronous generator (PMSG), is responsible for power generation in the DC microgrid. On the AC microgrid side, a PV power plant is responsible for generating a portion of the power in the AC/DC hybrid microgrid. Simulation results in the MATLAB Simulink environment demonstrate that employing hybrid storage maintains the DC microgrid voltage at its nominal value under continuous PV and wind power changes while accurately distributing power between AC and DC microgrids.